Organic geochemistry and kinetics for natural gas generation from mudstone and coal in the Xihu Sag, East China Sea Shelf Basin, China. (August 2020) - Cheng, Xiong; Hou, Dujie; Zhou, Xinhuai; Liu, Jinshui; Diao, Hui; Jiang, Yuhan; Yu, Zhongkun
Abstract: A comparative study on organic geochemistry and kinetics was performed on two representative coal measure mudstone and coal samples of the Eocene Pinghu Formation in the Xihu Sag, East China Sea Shelf Basin, China. Gas chromatography–mass spectrometry analysis of the aliphatic fractions of the source rock extracts was performed to characterize the maturity, depositional conditions, and source materials in the samples. The kerogens isolated from the mudstone and coal were pyrolyzed in a closed-system at two heating rates to determine the kinetics for natural gas generation, and the results were extrapolated to geological conditions. Biomarker assemblages show that the mudstone (type III kerogen) and coal (type II/III kerogen) contain predominantly terrigenous source materials with the effect of microbial reworking, and were deposited under oxic conditions within an unstratified water column. The mudstone has slightly more algal material input and less oxic conditions during deposition than the coal. The rocks are at the early-mature stage but the coal is slightly more mature than the mudstone. The activation energies for natural gas generation from the mudstone and coal distribute mainly in the range of 47–62 kcal/mol and 50–69 kcal/mol with a frequency factor of 2.0 × 10 11 s −1 and 1.0 × 10 13 s −1, respectively. The lower activation energies for the mudstone than the coal suggests an earlier onset of natural generation. Assuming a constant burial heating rate of 3 °C/Ma for the calculated activation energy distributions, the calculated temperature for a given transformation ratio can differ by > 60 °C, indicating varying kinetic stability due to different kerogen composition and structure. This significant and unexpected difference suggests that more attentions should be paid to the kinetic heterogeneity of coal bearing source rocks, and we must be particularly cautious about selecting appropriate kinetic models in petroleum system modeling. Highlights: Biomarker assemblages of coal measure mudstone and coal were analysed. Mudstone and coal were pyrolyzed to obtain kinetics for gas generation. Mudstone requires lower activation energy than coal for generating natural gas. Temperature for onset of gas generation by mudstone is lower than coal by 60 °C.